Optimizing Islamic Religious Education Learning with the Blended Learning Method - Hasan Albashri; Juliani; Nur Azizah; Devi Wahyu Ramadhani; Siti Zahara (Journal of Contemporary Islamic Primary Education, 2024)
Blended Learning is a learning facility that is carried out by combining various media in delivery methods, teaching models, and learning styles, with the help of information and communication technology appropriately to achieve the desired learning objectives. The pandemic period has seen the popularity of the blended learning approach. However, very few studies summarize the effectiveness of blended in different countries. Therefore, it is meaningful and necessary to examine the effectiveness of blended learning across the world. However, optimizing blended learning needs to be accompanied by adequate facilities and infrastructure as well as human resources. Both teachers and students must have technology-based knowledge to be able to use the facilities used in this blended learning method.